The Ccritical Sstudy of the book entitled “Ssociology of Stratificationstratums and Ssocial Iinequalities” book - Vakil ahmadi (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
The “Sociology of Stratification and Social Inequalities by Rasoul Rabani and Abraham Ansari was evaluated to improve human science resources. Of the book advantages are the study of social inequalities dimensions including such subjects as women and social stratum, religions and social stratum, ethnics and social inequalities, policy and social stratum as well as two chapters which deal with the case study of middle class in Iran and the USA. The formal generality factors have not been regarded as an educational book in university. The formal and content evaluation show that this book does not  meet the needs of a scientific society in sociology of stratum and social inequalities field despite of the third edition because the book is not problem-oriented; it has no theoretical presupposition and methodology, and its content has not been arranged around a main question, and if the book is subject–oriented, it is not an educational and scientific book, so it looks more like a collection of articles.